Advanced interstitial lung fibrosis with emphysema and pulmonary hypertension with no evidence for interstitial lung disease on high resolution CT. (1st July 2019) - Foris, Vasile; Brcic, Luka; Douschan, Philipp; Kovacs, Gabor; Stacher‐Priehse, Elvira; Olschewski, Horst
Abstract : The diagnosis of idiopathic pulmonary arterial hypertension (iPAH) is complex and, besides invasive hemodynamic evaluation, includes several diagnostic steps to exclude any underlying diseases. The role of a decreased diffusion capacity of the lung for carbon monoxide (DLCO) is a matter of discussion. Here, we present a 76‐year‐old man with a smoking history of 30 pack‐years who was diagnosed with iPAH after chronic thromboembolic pulmonary hypertension was excluded based on a negative perfusion scan, an underlying heart disease was excluded based on echocardiography and right heart catheterization, and a significant lung disease was excluded based on lung function test (FVC = 101% predicted, FEV1 = 104% predicted, FEV1/FVC = 77, TLC = 97% predicted) and thin‐slice computed tomography (CT) scan. Just DLCO was reduced to 40% predicted, suggesting a possible structural lung disease. Postmortem examination demonstrated severe interstitial lung fibrosis combined with microscopic emphysema. This indicates that both CT imaging and pulmonary function test may be insensitive to a diffuse peripheral combined pattern of fibrosis and emphysema and that DLCO may be the only sensitive marker of this significant lung pathology.